Molecular characterization by PCR-RFLP of indigenous fungal isolates from hypersaline stream water in România - Diguță, Camelia Filofteia; Proca, Irinel Gabriel; Jurcoane, Ștefana; Matei, Florentina (Folia microbiologica, 2019)
This is the first exhaustive report on the fungal community biodiversity in hypersaline water in România. A total of 27 fungal strains (19 molds and eight yeast) have been isolated from Lopătari hypersaline water, Buzau County. Based on classical investigation, these strains have been identified as belonging to the genera Aureobasidium, Alternaria, Aspergillus, Penicillium, and Fusarium. The molecular characterization of fungal isolates at species level was performed using PCR-RFLP analysis of the 5.8S-ITS region. PCR products were digested with different combinations of endonucleases. The most frequently isolated species were Aspergillus niger (14.81% of all isolates), A. versicolor, (14.81%) and Penicillium crustosum (14.81%). In addition, ribosomal restriction patterns which exhibited profiles specific to Aureobasidium pullulans were derived, and to discriminate between Aureobasidium isolates, the elongase-encoding gene (ELO) was chosen as a genetic marker followed by digestion with endonuclease HhaI. Five yeast isolates displayed restriction patterns corresponding to Aureobasidium melanogenum (18.52%) and three isolates to Aureobasidium pullulans (11.11%). In addition, the RFLP types of Aureobasidium pullulans varieties with HhaI are clearly distinguished and could be applied to assess the intraspecific variability.
Keywords: Rumunsko; Salt Tolerance; Romania; Ascomycota; biodiverzita; ribozomální DNA; DNA, Ribosomal; polymerázová řetězová reakce; houby; polymorfismus délky restrikčních fragmentů; tolerance k soli; Polymerase Chain Reaction; DNA, Fungal; Rivers; Yeasts; Phylogeny; Fungi; Polymorphism, Restriction Fragment Length; Aspergillus; kvasinky; Saline Waters; řeky; Biodiversity; Sequence Analysis, DNA; slané vody; DNA fungální; Water Microbiology; sekvenční analýza DNA; mikrobiologie vody; fylogeneze